2013
DOI: 10.1002/chem.201300992
|View full text |Cite
|
Sign up to set email alerts
|

TaMe3Cl2‐Catalyzed Intermolecular Hydroaminoalkylation: A Simple Complex for Enhanced Reactivity and Expanded Substrate Scope

Abstract: Tantalizingly simple: The common organometallic starting material TaMe3Cl2 can be used for the catalytic CH functionalization reaction, hydroaminoalkylation. The substrate scope for this readily accessed compound includes unactivated terminal and internal alkenes, styrene derivatives, and both alkylaryl‐ and dialkyl secondary amines (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
(20 reference statements)
4
39
0
Order By: Relevance
“…As can be seen from Table 1, the initial experiment performed under standard conditions {10 mol‐% [Ta(NMe 2 ) 5 ], hexanes, 140 °C, 96 h, sealed tube; Table 1, Entry 1}7g already gave access to the pure branched hydroaminoalkylation product 5a in 93 % isolated yield. Interestingly and in good agreement with the results obtained with group 5 metal catalysts with more complex ancillary ligands,8i8k the regioselectivity of the hydroaminoalkylation reaction was 98:2 in favor of the branched isomer 5a , as determined by GC analysis of the crude reaction mixture prior to chromatographic purification. A short optimization study then revealed that significantly lower yields of 5a are obtained at lower reaction temperatures of 120 or 100 °C (Table 1, Entries 2 and 3) or with shorter reaction times (16–72 h; Table 1, Entries 4–6).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As can be seen from Table 1, the initial experiment performed under standard conditions {10 mol‐% [Ta(NMe 2 ) 5 ], hexanes, 140 °C, 96 h, sealed tube; Table 1, Entry 1}7g already gave access to the pure branched hydroaminoalkylation product 5a in 93 % isolated yield. Interestingly and in good agreement with the results obtained with group 5 metal catalysts with more complex ancillary ligands,8i8k the regioselectivity of the hydroaminoalkylation reaction was 98:2 in favor of the branched isomer 5a , as determined by GC analysis of the crude reaction mixture prior to chromatographic purification. A short optimization study then revealed that significantly lower yields of 5a are obtained at lower reaction temperatures of 120 or 100 °C (Table 1, Entries 2 and 3) or with shorter reaction times (16–72 h; Table 1, Entries 4–6).…”
Section: Resultssupporting
confidence: 86%
“…The first successful hydroaminoalkylation reactions of styrenes catalyzed by group 5 metal catalysts have only been realized very recently with binaphtholate8i or phosphoramidate8j complexes as well as with [TaMe 3 Cl 2 ] 8k. In all of these cases, the branched product was always formed as the major regioisomer, and selected reactions could even be performed at room temperature 8j.…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose, ah ydroaminoalkylation reaction mixture of allylsilane 21 and N-methylaniline (1)i nt oluene was initially heatedt o1 40 8Cf or 24 hi nt he presence of 10 mol %o fc atalyst IV.A fterwards, 2.5 mol %P d 2 (dba) 3 ,7mol %R uPhos, sodium tert-butoxide and additional toluene were added and the resulting reactionm ixture was heatedt o1 10 8Cf or additional 24 h. The yield of 83 % in which 1,5-benzoazasilepine 23 was obtained after chromatographic purification ( Table 5, entry 1) again underlines the wellestablished fact that the Buchwald-Hartwig amination tolerates the presence of the reagents used in hydroaminoalkyla-tion reactions. To finally investigate the scope of the onepot procedure, we then reacteda dditional ortho-, meta-, and para-substituted N-methylanilines with allylsilane 21.A se xpecteda nd in good agreement with the results obtained for the hydroaminoalkylation of simple allylsilanes presented in Ta ble 2, it was found that para-o rmeta-substituted N-methylanilinesu ndergo smooth reactiont og ive the desired 1,5-benzoazasilepines in good yields between 66 and 84 %( Ta ble 5, entries [3][4][5][6][7][8][9][10][11]. To finally investigate the scope of the onepot procedure, we then reacteda dditional ortho-, meta-, and para-substituted N-methylanilines with allylsilane 21.A se xpecteda nd in good agreement with the results obtained for the hydroaminoalkylation of simple allylsilanes presented in Ta ble 2, it was found that para-o rmeta-substituted N-methylanilinesu ndergo smooth reactiont og ive the desired 1,5-benzoazasilepines in good yields between 66 and 84 %( Ta ble 5, entries [3][4][5][6][7][8][9][10][11].…”
Section: Resultssupporting
confidence: 71%
“…[7] The corresponding reaction sequence includes an initial highly regioselective titanium-catalyzed intermolecularh ydroaminoalkylation, [8,9] which takes place by the addition of an a-C(sp 3 )ÀHbond of an N-methylaniline across aC ÀCd ouble bond of an N-allyl-2-bromoaniline, and as ubsequenti ntramolecular Buchwald-Hartwig amination (Scheme 1, path A). [11] Interestingly,b yc hoosing allyl(2-bromophe-nyl)silanes as starting materials, the literature-unknown silicon analogues of 1,5-benzodiazepines, so-called 1,5-benzoazasilepines (Scheme 1, path B), should be accessible by ao ne-pot procedure that is similart oo ur 1,5-benzodiazepine synthesis. However,int his contextitm ust be noted that Schafer et al already achieved the hydroaminoalkylation of allyltrimethylsilane with N-methylanilineinthe presenceo fatantalum catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation